GAMBARAN EFEKTIVITAS PENERAPAN COGNITIVE BEHAVIOR THERAPY PADA KORBAN BENCANA DENGAN PTSD (POST-TRAUMATIC STRESS DISORDER) - Wati, Del Fatma; Wulan, Winda Ratna (REAL in Nursing Journal, 2018)
Disasters can cause trauma to individuals who experience direct events or as witnesses, which is one of the psychological impacts that are often encountered in disaster victims is Post-Traumatic Stress Disorder or PTSD. Pharmacological therapy in disaster victims with PTSD can be more effective if combined with psychotherapy interventions. One of the psychotherapy therapies that can be done using the CBT method. The goal of CBT is to improve psychosocial function, restore thinking ability, reduce the impact of traumatic events. The aim of this literature review is to determine the effectiveness of the application of CBT to disaster victims with PTSD, by using a database that is used as a search source related to research, namely "ncbi," google scholar ","msjonline.org"," national library ", and "Researchgate". Research data on databases using the keywords "disaster", "Post-Traumatic Stress Disorder (PTSD)", "Cognitive Behavior Therapy (CBT)", and "the influence of CBT". The results show that the CBT method used in disaster victims with PTSD is effective in reducing levels of anxiety, discomfort, depression, helplessness, and behavioral problems of various types of measuring instruments and different patient populations. This literature study reports that the positive influence of the CBT method used on disaster victims with PTSD can maintain adaptive coping, improve socialization and train courage of independence.Keywords: Disaster, Post-Traumatic Stress Disorder (PTSD), Cognitive Behavior Therapy (CBT), Effect of CBT